An An Analysis of Export Restriction Policies for Indonesian Nickel: Strengthening Indonesia's Opportunities from the European Union's Lawsuit Regarding Export Restrictions for Nickel: - Adi Gunawan; Nadir Nadir (LEGAL BRIEF, 2022)
Indonesia's international trade disputes do not just happen once. It has been recorded that Indonesia has entered the WTO's green table several times in the trade dispute settlement. Then, what needs attention is that the Indonesian government was defeated in the trial at the WTO in most of the many disputes facing Indonesia. The main reason for the defeat of the dispute was the weak arguments presented by representatives of the Indonesian government. Indonesia has entered a new lawsuit from the European Union at the WTO regarding the  Nickel Export Restriction with Dispute Settlement (DS) Complaint Number 592 on November 22, 2019, on the grounds of violating Article XI: I GATT agreement, related to the prohibition of quantitative restrictions. At the moment, the dispute must be won by Indonesia because it concerns the State's sovereignty regarding natural resources, which are very limited in number and cannot be renewed. This research objective was to provide input in ideas or statements in juridical theories and norms, which were strengthened by doctrines as a refutation of the allegations raised by the European Union in the WTO Session. Furthermore, this research used a normative juridical research method, with secondary data based on writings from some electronic mass media.